2018
DOI: 10.7251/agreng1701010p
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Types of European Importance in the Area of Wetlands Gromizelj (Bosnia and Herzegovina)

Abstract: The paper presents the types of wetlands habitat Gromizelj which is of Europeanimportance. The review is made on the basis of studies of flora and vegetation andthe Guide of the types of habitats according to the European Union (EU) HabitatsDirective. Swamp Gromizelj is located in the northeast of Republic of Srpska (RS)and Bosnia and Herzegovina (BiH), in the municipality of Bijeljina. During theresearch the following habitats have been isolated: 3150 Natural eutrophic lakeswith Magnopotamnion-or Hydrochariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the scale of South-Eastern Europe, a single alliance only, Senecionion fluviatilis (syn. Convolvulion sepium), has been reported from Albania [33], Bosnia and Herzegovina [34], Croatia [35], Serbia [36], and Slovenia [37]. The same is true for Hungary [38] and Eastern Transylvania [39].…”
Section: The General Pattern Of Tall Herb Vegetation and Its Relation...mentioning
confidence: 86%
“…On the scale of South-Eastern Europe, a single alliance only, Senecionion fluviatilis (syn. Convolvulion sepium), has been reported from Albania [33], Bosnia and Herzegovina [34], Croatia [35], Serbia [36], and Slovenia [37]. The same is true for Hungary [38] and Eastern Transylvania [39].…”
Section: The General Pattern Of Tall Herb Vegetation and Its Relation...mentioning
confidence: 86%
“…Thus, in the Gromiţelj protected habitat, newly registered spider species were also found in the following internationally significant habitats bearing the following designations: 3270 (Muddy river banks with Chenopodimnionor and Bidention p.p. Vegetation), 6430 (Hydrophilus tall-herb fringe communities of plains and of the montane to alpine levels), Reedbeds (tall sedges and vegetation of Phragmito-Magnocaricetea), 91E0 (Alluvial forest with Alnus glutinosa and Fraxinus excelsior (Alno-Padion, Alnion incanae, Salicion albae)) i 91F0 (Riparian mixed forest of Quercus robur, Ulmus laevis and Fraxinus sp., along large rivers (Ulmenion minoris)[47].According to data on the Fauna of Europe, all species except Lycosa singoriensis are found in Slovenia, Croatia, Serbia and Montenegro, while the species mentioned is not listed for Croatia but only for Slovenia, Serbia and Montenegro. According toGrbac, et al (2019), specimens of all eight species are found in the Araneae collection in the Croatian Natural History Museum in Zagreb, which was founded in 1931 and includes material collected between 1884 and 1964.…”
mentioning
confidence: 99%